2009
DOI: 10.1128/iai.00840-08
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 9-Dependent Activation of Myeloid Dendritic Cells by Deoxynucleic Acids fromCandida albicans

Abstract: The innate immune system of humans recognizes the human pathogenic fungus Candida albicans via sugar polymers present in the cell wall, such as mannan and ␤-glucan. Here, we examined whether nucleic acids from C. albicans activate dendritic cells. C. albicans DNA induced interleukin-12p40 (IL-12p40) production and CD40 expression by murine bone marrow-derived myeloid dendritic cells (BM-DCs) in a dose-dependent manner. BM-DCs that lacked Toll-like receptor 4 (TLR4), TLR2, and dectin-1, which are pattern recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 54 publications
5
74
2
2
Order By: Relevance
“…27 Similarly, using high dose challenges, TLR9-/-mice showed no significant alteration in survival upon clinical C. albicans isolate infection. 25,27 However, increased susceptibility to systemic candidiasis and impaired fungal clearance in TLR9-/-mice were observed upon challenge with a lower dose of C. albicans. 27 Taylor PR et al 184 investigatedb-glucan recognition and control of fungal infection using Dectin1-/-mice, and revealed that cytokine release, phagocyte recruitment, phagocytosis and microbial killing are all impaired in the Dectin1-/-mice compared with wild-type mice in disseminated candidiasis model.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micementioning
confidence: 99%
See 3 more Smart Citations
“…27 Similarly, using high dose challenges, TLR9-/-mice showed no significant alteration in survival upon clinical C. albicans isolate infection. 25,27 However, increased susceptibility to systemic candidiasis and impaired fungal clearance in TLR9-/-mice were observed upon challenge with a lower dose of C. albicans. 27 Taylor PR et al 184 investigatedb-glucan recognition and control of fungal infection using Dectin1-/-mice, and revealed that cytokine release, phagocyte recruitment, phagocytosis and microbial killing are all impaired in the Dectin1-/-mice compared with wild-type mice in disseminated candidiasis model.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micementioning
confidence: 99%
“…147 Moreover, it is suggested that C. albicans activates murine bone marrow-derived myeloid DCs through a TLR9-mediated signaling pathway. 25 Dectin-1 was well characterized on DCs. It was found that Dectin-1 was high expressed on the DC cell line XS52, but less on the macrophage cell line J774.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…In these activities, b-glucan receptors cooperate, to different extents, with Toll-like receptor 2 (TLR2) [8]. Moreover, fungal mannans are detected by several PRRs [9], whereas fungal DNA is recognized by TLR9 [10,11].It is presently unclear whether fungal recognition induces activation of the type I interferon (IFN) system, which regulates the expression of many genes and is therefore considered a fundamental arm of the innate immune system [12,13]. The type I IFN family includes the single IFN-b and many IFN-a subtypes that activate a common receptor (IFN-a/b receptor or IFNAR), composed of two subunits, IFNAR-I and IFNAR-II.…”
mentioning
confidence: 99%